ANTHRAX GLOBAL EPIZOOTOLOGY. 1. SUSCEPTIBLE ANIMALS - Makhamat Nguerabe Yamtitina; V. V. Makarov (Ветеринария сегодня)
Anthrax is a widespread disease. Epizootic outbreaks are constantly registered worldwide. Obligatory lethality of the disease, the causative agent of which leads a parasitic mode of life, makes it possible to consider mortality as the main sign of anthrax epizootic process in animals. The paper describes susceptibility of animals to anthrax under natural conditions. The paper presents literature data on the participation of animals of diﬀerent species and groups in the epizootic process, and the author’s own results of analysis of the recent situation. The susceptibility of animal species to anthrax depends not only on the dose, but also on the form (vegetative or spore) of the anthrax bacterium, the mode of infection, and the site of introduction of the pathogen into the organism. Anthrax aﬀects mammals of 19 species: mostly cattle, which are intermediate hosts and hosts in the global parasitoid system; sheep and goats, horses, pigs, many species of wild ruminants and herbivorous, mostly deer, gazelles, bisons, hippopotamuses and even elephants, as well as Carnivora. Herbivorous endemic animals play the main role in maintenance of natural (soil) foci of anthrax and provide infectious cycles and regular recontamination of the soil – the only reservoir of infection. Such multipathogenicity demonstrates the predominant host range of local parasitoid systems – cattle and small ruminants in the areas of pasture, distant-pasture, free-range cattle rearing (Africa, Asia, Australia), wild herbivores in Africa and the south of the USA, bisons in Canada, deer in the north of the Russian Federation. Infection of Equidae and particularly predators has a sporadic, dead-end character. It occurs relatively seldom and does not play any signifcant role in anthrax epizootology and epidemiology.